Luxury brand commitment: a study of Chinese consumers. Issue 7 (30th September 2014) - Li, Ning; Robson, Andrew; Coates, Nigel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to assess brand commitment levels demonstrated by luxury brand consumers in China and seeks to identify the most significant combination of antecedents from brand affect, image, value and trust. Design/methodology/approach – A self-completion, researcher-supported questionnaire was disseminated within four Beijing shopping malls, generating 501 participants. The questionnaire comprised a range of scale sets covering brand affect, image, value, trust and commitment. The analysis comprised a summary overview of brand attainment followed by a substantive analysis involving confirmatory factor analysis and structural equations modelling to identify the most significant combination of antecedents relating to brand commitment. Findings – Regarding absolute consumer endorsement, brand affect was the most positive area, with image, trust and value representing relatively positive brand attributes. Declared commitment was relatively low, representing a potential commercial challenge. Value, represented by its social and symbolic components, and trust were identified as providing a significant and direct explanation of consumer commitment, represented by its affective and continuance dimensions. The role of value and trust must be central in marketing luxury brands given their direct and combined impact on consumer commitment. Research limitations/implications – The findings are transferable to other "Tier 1" locations in China, but take no account of either consumer behaviour outside of these wealthier conurbations, or segmentation of the associated markets. Originality/value – Geographic setting and consideration of a vast consumer group provides research value and contribution to marketing planning in the pursuit of higher levels of consumer commitment to their brands.